2019
DOI: 10.1002/aoc.4988
|View full text |Cite
|
Sign up to set email alerts
|

A highly selective multifunctional Zn‐coordination polymer sensor for detection of Cr (III), Cr (VI) ion, and TNP molecule

Abstract: A new coordination polymer based on the 4-(2,2′;6′,2″-tripyridyl)-4′-1,2-phenyl dicarboxylic acid (H 2 tbda), namely, [Zn (tbda)] n (1), features a onedimensional binuclear chain structure and exhibits the excellent luminescence in pH range of 3-12 in aqueous solution. Particularly, compound 1 shows the remarkable selectivity, anti-interference, and recyclability for sensing Cr (III) ion through the fluorescence enhancement. Meanwhile, compound 1 can also serve as a sensor for detecting the trace amounts of Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Under solvothermal conditions (DMF/H 2 O, 160 °C), ZnSO 4 ·6H 2 O and H 2 8 combine to give [Zn( 8 )] n ( Figure 6 b). The presence of the two CO 2 – groups per ligand facilitates the assembly of a double-stranded chain [ 33 ]. This may be compared to the double-stranded chain found in [ZnCl( 4 )] n ·[ZnCl(OH 2 )( 4 )] n ( Figure 5 e), but the additional carboxylate groups lead to distinct differences in the dinuclear building blocks in the 1D-chain.…”
Section: 22′:6′2″-terpyridinementioning
confidence: 99%
“…Under solvothermal conditions (DMF/H 2 O, 160 °C), ZnSO 4 ·6H 2 O and H 2 8 combine to give [Zn( 8 )] n ( Figure 6 b). The presence of the two CO 2 – groups per ligand facilitates the assembly of a double-stranded chain [ 33 ]. This may be compared to the double-stranded chain found in [ZnCl( 4 )] n ·[ZnCl(OH 2 )( 4 )] n ( Figure 5 e), but the additional carboxylate groups lead to distinct differences in the dinuclear building blocks in the 1D-chain.…”
Section: 22′:6′2″-terpyridinementioning
confidence: 99%
“…[12][13][14][15] Under this background, some MOFs were synthesized and structurally analyzed, which show luminescence sensing properties for the probe of Fe 3+ , CrO 4 2À , Cr 2 O 7 2À , CS 2 , nitroaromatic explosives with high selectivity and sensitivity. [16][17][18][19] On the other hand, cadmium is a toxic metal, which has lesser value in medicinal chemistry, but the study on the drug activity of such compound would pave way to understand the structural requirements or the role of a metal ion in drugs. Recent studies in the literature have revealed that some Cd(II)-based coordination complexes show interesting bioactivity.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…5g and h) for Cr 2 O 7 2− showed almost linear correlation at low concentrations ( R 2 = 0.9895 for 1 and 0.9927 for 2 ), and the K sv values are 3.95 × 10 3 M −1 for 1 and 3.53 × 10 3 M −1 for 2 . The detection limits were calculated to be 5.81 ppm for 1 and 14.73 ppm for 2 , which might be compared with other well-designed sensing materials (4.75–32.4 ppm), 21 a ,22 suggesting that 1 and 2 are efficient sensors for detecting Cr 2 O 7 2− in aqueous media.…”
Section: Resultsmentioning
confidence: 94%